Process design and experimental study on drilling operations of a hybrid aluminum/carbon fiber reinforced polymer/titanium composite - Kayihan, Mete; Karaguzel, Umut; Bakkal, Mustafa (TAYLOR & FRANCIS INC, 2024)
Carbon fiber reinforced composites (CFRP) are increasingly used in aviation and automotive industries. To enhance rigidity and fatigue resistance, aluminum (Al) and titanium (Ti) alloys are used together with CFRP materials. Drilling is a common method for manufacturing these hybrid composite stacks. This study examines the impact of process parameters, temperature, tool wear, thrust force, and torque on CFRP/Al/Ti hybrid composites during dry machining. Tests were conducted at various drilling speeds, feed rates, and stack orders using a solid carbide (WC) cutting tool. Results indicate that feed rate has a significant effect on the process outputs. The temperature remains low as the feed rate rises. The delamination factor is the highest in the Ti\CFRP\Al stack. In addition, delamination and temperature rise with increasing cutting speed. Finally, while the Al\CFRP\Ti stacking order performs poorly in terms of tool wear, it is measured more than 330 micrometers at the lowest feed rate.
Keywords: Hybrid stacks; hybrid composites; thrust forces; delamination factor; temperature; cutting parameters; tool wear; CFRP; titanium; aluminum; Taguchi; HOLE QUALITY; DELAMINATION; STACKS; Engineering; Materials Science